BUSINESS INTELLIGENCE IMPLEMENTATION FOR CULINARY MSMES: A CASE STUDY OF DIGITAL BUSINESS TRANSFORMATION IN PRINGSEWU CITY - Sri Hartati; Ario Rinaldi; Rina Wati; Meinhaj Hussain (JMBI (Journal of Marketing and Business Intelligence), 2026)
This study examines the implementation of Business Intelligence (BI) in culinary Micro, Small, and Medium Enterprises (MSMEs) in Pringsewu as part of digital business transformation efforts. The main problem faced by culinary MSMEs is the limited use of data-driven decision-making due to manual transaction recording, low digital literacy, and the absence of analytical tools for monitoring business performance. This research employed a descriptive qualitative case study approach involving 15 culinary MSMEs. Data were collected through interviews, observations, documentation, and sales transaction analysis using a simple BI dashboard. The novelty of this study lies in the practical implementation of a low-cost and user-friendly Business Intelligence model specifically designed for local culinary MSMEs. The results indicate that BI implementation improved sales monitoring, customer analysis, product trend identification, and business decision-making effectiveness. Furthermore, the dashboard contributed to a 12.5% increase in sales turnover and enhanced operational efficiency among participating MSMEs.